SUMATRAN FLEABANE CONTROL USING GLYPHOSATE IN ASSOCIATION WITH HALAUXIFEN-METHYL FORMULATIONS - Zobiole, L. H. S. (2018)
The effectiveness of a new product has a great importance to weed control, especially those that are difficult to control or resistant to, such as the sumatran fleabane (Conyza sumatrensis). The objective of this research was to evaluate the control of C. sumatrensis at different growth stages, using halauxifen-methyl in combination with other herbicides. The experimental design used was a randomized blocks in a 3x10 factorial scheme, with four replications. The plants of C. sumatrensis were evaluated at different growth: stage 1: plants with 8 leaves; Stage 2: plants with 19 leaves and stage 3: plants with 45 leaves fully expanded. The herbicides used were the association of glyphosatc with the herbicides 2,4-D at 806, 943 and 1,209 g a.e. ha(-1), halauxifen-methyl + diclosulam at 5.06 g a.e. ha(-1) + 25.52 g a.i. ha(-1) and 6.32 g a.e. ha(-1) + 31.87 g a.i. ha(-1), halauxifen-methyl+ 2,4-D at 5.00 + 783 g a.e. ha(-1) and 6,0 + 940 g a.e. ha(-1) and halauxifen-methyl at 5.0 and 6.0 g a.c. ha(-1) and untreated, totaling 10 treatments. The herbicides demonstrated satisfactory control of the plants in Stage 1 at 50 DAA, with the exception of the glyphosate + 2,4-D treatment at the lowest rate. However for Stages 2 and 3 the halauxifen-methyl + diclosulam in both rates, provided superior controls in relation to the other treatments. The control of sumatran fleabane was facilitated when their management occurs in the early stages of development, however independent of the development stage, the best controls obtained were with the treatment containing glyphosate + halauxifen-methyl + diclosulam at 1,440 g a.c. ha(-1) + 6.32 g a.e. ha(-1) + 31.87 g a.i. ha(-1). Thus, combinations of herbicides containing halauxifen-methyl arc another option to control C. sumatrensis in agricultural systems.